PENGARUH JUMLAH PENDUDUK, INVESTASI DAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BOGOR PERIODE 2016-2019 - Zeze Zakaria Hamzah; Nida Siti Anggraeni (Institut Teknologi dan Bisnis Dewantara, 2021)
The population continues to increase but the percentage increase in regional original income that tends to decrease is certainly a concern for researchers. The purpose of this study was to determine the effect of population, investment, and local tax revenue together on Regional Original Income in Bogor Regency for the period 2016-2019. The results showed 1. The results of the test t prove that the total population does not have a positive and significant effect on Regional Original Income in the Regional Government of Bogor Regency, this is evidenced by the t value of -0.572 <t table 2.718 and the significance value of 0.578> 0 , 05. 2. The results of the test partially prove that partially the investment does not have a positive and significant effect on Regional Original Income in the Regional Government of Bogor Regency. This is evidenced by the t value -0.733 <t table 2.718 and the significance value 0.477> 0.05. 3. The test results simultaneously prove that together the independent variables consisting of total population, investment, and local taxes simultaneously had a positive and significant effect on Regional Original Income in Bogor Regency.